The photo-redox of chromium regulated by microplastics (MPs) and MPs-derived dissolved organic matter (MPs-DOM) and the CO2 emission of MPs-DOM - Enyao Zhang; Yalan Chen; Yang Li; Ke Sun; Yan Yang; Bo Gao; Baoshan Xing (Fundamental Research)
Microplastics (MPs) and chromium (Cr) are common pollutants in wastewater treatment plants, where ultraviolet disinfection processes may degrade MPs and photooxidize Cr(III) into more hazardous Cr(VI). In this study, the effects of MPs on the phototransformation of coexisting Cr, as well as the role and ecological effects of MPs-derived dissolved organic matter (MPs-DOM), were investigated. The photooxidation of MPs and Cr(III) was radical-driven reaction. The addition of MPs inhibited the photooxidation of Cr(III) and induced the photoreduction of Cr(VI) through surface adsorption. Both MPs and MPs-DOM generated comparable ROS at different irradiation moments, which can affect the photodegradation of MPs and MPs-DOM, as well as the phototransformation of Cr. The 56-day incubation showed a higher mineralization ratio of MPs-DOMs than riverine humic acid, indicating the vital contribution of MPs-DOMs to carbon emissions. In general, MPs-DOM lowered microbial abundance and diversity compared to the original inoculum. Bacterial and fungal succession was affected by both MPs-DOM and the original inoculum, with polyvinyl chloride-derived DOM possessing a stronger filtration impact on microbial communities than the other three MPs-DOMs. In this study, a win–win solution for Cr(VI) reduction and MPs treatment through photoirradiation was proposed, and the potential significant role of MPs-DOM in the transformation of coexisting contaminants, the carbon cycle, and microbial succession was highlighted.